Hardware-in-the-loop validation of speed synchronization controller for a heavy vehicle with Hydraulics AddiDrive System. (April 2018) - Song, Dafeng; Li, Lixin; Zeng, Xiaohua; Li, Sheng; Li, Guanghan; Li, Gaozhi; He, Hui; Li, Xianghua
A novel Hydraulics AddiDrive System consisting of a variable displacement pump and two in-wheel motors is presented. The new Hydraulics AddiDrive System installed on the front axle of a traditional rear-wheel drive heavy vehicle aims to offer better mobility and improve traction efficiency in rough driving condition. To synchronize speeds between front in-wheel motors and rear wheels for optimal traction efficiency, a speed synchronization controller composed of feedforward and feedback control strategy is proposed for displacement adjustment of the variable displacement pump. The feedforward strategy is designed based on the relationship between the displacement coefficients of variable displacement pump and the gears. The feedback strategy utilizes proportional–integral algorithm to correct the dynamic errors. The compound speed synchronization controller helps to improve the control accuracy and adaptability under varied external conditions. Simulations are conducted on AMESim and MATLAB/Simulink to validate the proposed control strategy. The hardware-in-the-loop test allows for a more realistic evaluation of the proposed strategy, providing guidance of its application in real vehicle. Simulation and experiment results indicate that the maximum gradeability and traction force can be separately increased by 14.4%–17.2% and 13.4%–15.6% at low adhesion coefficient roads. The speed of front and rear wheel can be matched accurately with small difference below 1.31%.